MENGUKUR KEPUASAN MAHASISWA TERHADAP PELAYANAN BAAK AMIK AKMI BATURAJA - Echi Kurniati; Kadarsih Kadarsih (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
The purpose of this study is to find out how big the level of student satisfaction to the service BAAK AKMI Baturaja for this. The benefits of this research is as an information and evaluation material for BAAK on the efforts that have been done in providing services to students. This research uses descriptive method with quantitative approach. The service measurement indicators used are Tangibles, Reliability, Responsiveness, Assurances, Empathy. Through this research obtained Tangible value = 40.32%, Responsiveness = 20.24% and Reliability = 19.62%. The result of the measurement of student satisfaction on the service quality of BAAK is good. However, on the Empathy indicator = 6.45% means that there is a need for improvement in order to match the results and the promise of service. So also on indicators Assurance = 13.37% still need an increase in service by officers to students.